DESERTIFICATION - A MASS PHENOMENON THAT CONTRIBUTES TO SOIL DEGRADATION - Roxana – Gabriela POPA (Fiabilitate şi Durabilitate, 2018)
Desertification is a complex phenomenon, due to natural and anthropogenic causes, on vulnerable ecosystems in arid, semi-arid and dry sub-areas. The paper presents aspects of desertification, as a phenomenon of scale, at a global level, at the level of Romania, at the level of Oltenia and at the level of Gorj county. At the level of our country, the 11 counties in which global warming and drought will be ravaged in the following years are Timis, Mehedinti, Dolj, Olt, Teleorman, Giurgiu, Calarasi, Ialomita, Giurgiu, Galati and Vaslui, temperature increase and decrease the amount of rainfall being the main factors causing the desertification.